RESPON MACAM PUPUK ORGANIK DAN MACAM MULSA TERHADAP HASIL TANAMAN SAWI CAISIM (Brassica juncea, L.) Var. Tosakan - Nurul Azizah; Gembong Haryono; Tujiyanta Tujiyanta (Universitas Tidar, 2016)
Research on the response of sorts and kinds of organic fertilizer mulch on crop yields caisim mustard (Brassica juncea L.) var. Tosakan been conducted from October to December 2014 in the hamlet Paingan, Mangunrejo Village, District Tegalrejo, Magelang. Altitude of 800 m above sea level studies and types of soil with a pH of 6.5 latosol. The method used was factorial with complete randomized block design consisting of two factors. The first factor is the kind of organic fertilizer (P), consisting of no fertilizer (Po), cow manure (P1) and manure goat (P2), the second factor is the kind of mulch (M) consisting of mulch black silver (M1), straw mulch (M2) and bamboo leaf mulch (M3).The results showed that the effect on the kinds of organic fertilizer plant height, number of leaves per plant, leaf weight per plant consumption, heavy consumption of leaves per plot and leaf area per plant, but has no effect on the weight of fresh roots per plant. Kind of care mulch affect plant height, number of leaves and leaf weight per plant consumption, but has no effect on the weight of leaf consumption per plot, leaf area per plant and fresh weight of roots per plant. There is no interaction between the kinds of organic fertilizers and mulch sorts against the weight of leaves per plant consumption.